Doxorubicin loaded ferritin nanoparticles for ferroptosis enhanced targeted killing of cancer cells. Issue 49 (10th September 2019) - Yang, Runlin; Li, Yaoqi; Wang, Xinyu; Yan, Junjie; Pan, Donghui; Xu, Yuping; Wang, Lizhen; Yang, Min
Abstract : DOX loaded ferritin selectively induces ferroptosis enhanced killing of transferrin receptor 1 overexpressed cancer cells. Abstract : In recent years, ferroptosis has been investigated widely as a new form of cell death. Development of nanodrugs for ferroptosis induction in cancer cells may be a promising approach for cancer treatment. Here, we developed a type of nanoparticle consisting of the antitumor drug doxorubicin and exogenous ferritin. The drug loading process did not change the size of ferritin obviously. And this nanoparticle could induce the accumulation of ROS and cell ferroptosis for transferrin receptor overexpressed tumor cell, HT29. The ferroptosis process was also confirmed using inhibitors for ferroptosis. The cytotoxicity of this nanoparticle is similar to that of free DOX. This study provides a new strategy for targeting and killing transferrin receptor overexpressed tumor cells.